2016
DOI: 10.1111/jnc.13519
|View full text |Cite
|
Sign up to set email alerts
|

Selective up‐regulation of functional mu‐opioid receptor splice variants by chronic opioids

Abstract: We recently reported (Verzillo, et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 84 publications
(174 reference statements)
3
8
0
Order By: Relevance
“…) strongly suggests that increased association of MOR‐1B2 and MOR‐1C1 with G s α following chronic morphine was functional. This manifestation of increased MOR G s signaling is consistent with our earlier report that chronic morphine treatment can differentially stimulate GTPγS binding (a measure of functional coupling) by MOR‐1B2 and MOR‐1C1, but not MOR‐1 (Chakrabarti et al ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…) strongly suggests that increased association of MOR‐1B2 and MOR‐1C1 with G s α following chronic morphine was functional. This manifestation of increased MOR G s signaling is consistent with our earlier report that chronic morphine treatment can differentially stimulate GTPγS binding (a measure of functional coupling) by MOR‐1B2 and MOR‐1C1, but not MOR‐1 (Chakrabarti et al ).…”
Section: Resultssupporting
confidence: 92%
“…More recently, we reported that mRNA and protein corresponding to both MOR‐1B2 and MOR‐1C1 are up‐regulated in spinal cord (of males) following chronic systemic morphine (Chakrabarti et al ; Verzillo et al ). This study demonstrates that the association of MOR‐1B2 and MOR‐1C1 with G s α is significantly augmented after chronic treatment with morphine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations